Compilation Guidelines for Measurement of Gender-in-trade Statistics - UN Trade; Development (United Nations, 2025)
The Compilation Guidelines for Measurement of Gender-in-Trade Statistics were prepared by UNCTAD for further refinement and application in country pilot studies to assess data availability and gaps, and to compile experimental gender-in-trade indicators. The compilation guidelines reflect on the findings of a pilot carried out in Georgia, and later repeated in Kazakhstan. The guidelines were produced as part of the joint UNCTAD-ECA-ECE United Nations Development Account project “Data and statistics for more gender-responsive trade policies in Africa, the Caucasus, and Central Asia